2015
DOI: 10.1039/c5cp04368a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene with nanopores on metal clusters

Abstract: Porous graphene, which is a novel type of defective graphene, shows excellent potential as a support material for metal clusters. In this work, the stability and electronic structures of metal clusters (Pd, Ir, and Rh) supported on pristine graphene and graphene with different sizes of nanopores were investigated using first-principles density functional theory (DFT) calculations. Then, CO adsorption and oxidation on the Pd-graphene system were chosen to evaluate its catalytic performance. Graphene with nanopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The surface atom arrangement and nonideal structure of substrates, such as lattice variation, mechanical strain, defects and functional groups, are also crucial factors for controlling the morphology of metal NPs. Figure a shows the structure of Ni and Cu NPs supported on various atomically smooth van der Waals surfaces.…”
Section: The Thermal Stability Of Supported Metal Nanoparticlesmentioning
confidence: 99%
“…The surface atom arrangement and nonideal structure of substrates, such as lattice variation, mechanical strain, defects and functional groups, are also crucial factors for controlling the morphology of metal NPs. Figure a shows the structure of Ni and Cu NPs supported on various atomically smooth van der Waals surfaces.…”
Section: The Thermal Stability Of Supported Metal Nanoparticlesmentioning
confidence: 99%
“…Not just in regard to the stability, the electron character of the metal also might be influenced a lot when metal clusters were embedded in the porous graphene, which was revealed by the study of theoretical calculations particularly. Wang et al investigated electronic structures of metal clusters (Pd, Ir, and Rh) supported on pristine graphene and porous graphene with density functional theory (DFT) calculations and reported that graphene with nanopores could stabilize the metal clusters, downshift the d-band center of the metal clusters, and change the binding energy of reagents substantially …”
Section: Introductionmentioning
confidence: 99%
“…Wang et al investigated electronic structures of metal clusters (Pd, Ir, and Rh) supported on pristine graphene and porous graphene with density functional theory (DFT) calculations and reported that graphene with nanopores could stabilize the metal clusters, downshift the d-band center of the metal clusters, and change the binding energy of reagents substantially. 24 What is more, the porous graphene itself exhibits special electron or adsorption properties because of the abundant defective carbon atoms along the pores. For example, several works proved that the reaction rate of methane decomposition catalyzed by defective carbon materials was linearly dependent on the number of −CHCH− defective sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Owing to the abundant functional groups of their organic linkers, MOF supports have the potential to manipulate catalytic properties either geometrically or electronically. Although other supports (e.g., carbon, metal oxides,, and zeolites) have been studied widely, the effects of the support on NMC/MOFs have not been reported until now.…”
Section: Introductionmentioning
confidence: 99%